The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1128/jcm.30.4.987-992.1992
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a one-step and a two-step polymerase chain reaction with degenerate general primers in a population-based study of human papillomavirus infection in young Swedish women

Abstract: The prevalence of human papillomavirus (HPV) infection in cervical cell scrapes from young women was determined by polymerase chain reaction (PCR) by using general primer pairs localized within the Li region. With a one-step general PCR, 5.9%Yo (35 of 590) of young women in a population-based study were found to contain HPV DNA. The proportion of HPV-positive women increased with age, from 1.4% (1 of 69) among women aged 19 years to 9.2% (13 of 142) among women aged 25 years. Among the cervical scrapes from wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
6

Year Published

1993
1993
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(46 citation statements)
references
References 30 publications
2
34
1
6
Order By: Relevance
“…In order to identify the HPV types in the HR-HPVnegative lesions we analyzed more than 2000 genital specimens obtained from approximately 800 patients using an HPV detection and typing system that includes all genital HPV types. Despite the higher risk of false positive results a nested PCR was performed since one step amplification using MY9/MY11 primers was shown to be of limited sensitivity (22,23,26) . Accordingly, in the present study, around one third of all HPV infections were identified after nested PCR only.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify the HPV types in the HR-HPVnegative lesions we analyzed more than 2000 genital specimens obtained from approximately 800 patients using an HPV detection and typing system that includes all genital HPV types. Despite the higher risk of false positive results a nested PCR was performed since one step amplification using MY9/MY11 primers was shown to be of limited sensitivity (22,23,26) . Accordingly, in the present study, around one third of all HPV infections were identified after nested PCR only.…”
Section: Discussionmentioning
confidence: 99%
“…To efficiently identify HPV 16 variants in low-copy number HPV DNA, nested PCR was performed. The conditions used were as previously described (14,15) .…”
Section: Detecting Hpv 16 Infection By Polymerase Chain Reactionmentioning
confidence: 99%
“…They conclude that the use of the MY/GP nested PCR increased significantly the positivity rate of HPV DNA detection and should be used for samples with a low copy number of HPV DNA. Evander et al (31) compared the results obtained with MY, GP, and nested MY/GP primers. There were 56.5% specimens negative with MY and positive only with GP primers.…”
Section: Pcr Versus Morphological Criteriamentioning
confidence: 99%